Disclosure of Small Profits by BM&FBOVESPA Stock Exchange Listed Companies - Decourt, Roberto Frota (2018)
The present study sought to verify the normal curve distribution modality for returns on equities from companies listed on the BM&FBOVESPA Stock Exchange in order to search for evidence of earnings management in financial statements from 1995 to 2012. Although small profits or losses have a slightly different in rational logic, the difference between declared profit and loss can be significant psychologically. In this way, companies would avoid reporting small losses, thus transforming them into profits. The method used was based on the work of Burgstahler and Dichev (1997), in which profits histograms were analyzed for the frequency of small negative and positive relations in equity variations. The results emphasized the practice of results management more consistently between 1995 and 2012, nevertheless this undesirable practice has been declining in Brazil.